Regionalizacija Slovenije - Ravbar, Marjan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
We analyze the factors influencing the success of regionalization in the operation of the decentralization policy, in particular the formation of clear political and legal frameworks for reform process, the precise designation of strong and, if feasible, interdisciplinary commissions for administering the decentralization process, the formation of a concept of decentralized regionalization for Slovenia that aims at the even division of tasks and responsibilities including clear forms of reciprocal coordination and control among the various regional and national levels, and finally the taking of measures to guarantee the professional ability of institutions and decentralized regional associations to undertake new tasks.
Keywords: decentralizacija; regije; regionalizacija; regionalni razvoj; Slovenia; Slovenija